No Association of IFNL4 Genotype With Opportunistic Infections and Cancers Among Men With Human Immunodeficiency Virus 1 Infection. (27th December 2022) - Fang, Michelle Z; Jackson, Sarah S; Pfeiffer, Ruth M; Kim, Eun-Young; Chen, Sabrina; Hussain, Shehnaz K; Jacobson, Lisa P; Martinson, Jeremy; Prokunina-Olsson, Ludmila; Thio, Chloe L; Duggal, Priya; Wolinsky, Steven; et al.
Abstract: Background: IFNL4 genetic variants that are strongly associated with clearance of hepatitis C virus have been linked to risk of certain opportunistic infections (OIs) and cancers, including Kaposi sarcoma, cytomegalovirus infection, and herpes simplex virus infection. As the interferon (IFN) λ family plays a role in response to viral, bacterial, and fungal infections, IFNL4 genotype might affect risk for a wide range of OIs/cancers. Methods: We examined associations between genotype for the functional IFNL4 rs368234815 polymorphism and incidence of 16 OIs/cancers among 2310 men with human immunodeficiency virus (2038 white; 272 black) enrolled in the Multicenter AIDS Cohort Study during 1984–1990. Our primary analyses used Cox proportional hazards models adjusted for self-reported racial ancestry to estimate hazard ratios with 95% confidence intervals, comparing participants with the genotypes that generate IFN-λ4 and those with the genotype that abrogates IFN-λ4. We censored follow-up at the introduction of highly effective antiretroviral therapies. Results: We found no statistically significant association between IFNL4 genotype and the incidence of Kaposi sarcoma (hazard ratio, 0.92 [95% confidence interval, .76–1.11]), cytomegalovirus infection (0.94 [.71–1.24]), herpes simplex virus infection (1.37 [.68–2.93]), or any other OI/cancer. We observed consistent results using additive genetic models and after controlling for CD4 cell count through time-dependent adjustment or restriction to participants with a low CD4 cell count. Conclusions: The absence of associations between IFNL4 genotype and these OIs/cancers provides evidence that this gene does not affect the risk of disease from opportunistic pathogens. Abstract : Previous studies reported associations between IFNL4 genetic variants and the risk of certain opportunistic infections and cancers, but we found no associations between IFNL4 rs368234815 genotype and any of 16 opportunistic infections and cancers among men enrolled in a large cohort study.